Semi-random multicore fibre design for adaptive multiphoton endoscopy - Kim,Y; Warren,S; Favero,F; Stone,J; Clegg,J; Neil,M; Paterson,C; Knight,J; French,P; Dunsby,CW (Optics Express, 2018)
This paper reports the development, modelling and application of a semi-random multicore fibre (MCF) design for adaptive multiphoton endoscopy. The MCF was constructed from 55 sub-units, each comprising 7 single mode cores, in a hexagonally close-packed lattice where each sub-unit had a random angular orientation. The resulting fibre had 385 single mode cores and was double-clad for proximal detection of multiphoton excited fluorescence. The random orientation of each sub-unit in the fibre reduces the symmetry of the positions of the cores in the MCF, reducing the intensity of higher diffracted orders away from the central focal spot formed at the distal tip of the fibre and increasing the maximum size of object that can be imaged. The performance of the MCF was demonstrated by imaging fluorescently labelled beads with both distal and proximal fluorescence detection and pollen grains with distal fluorescence detection. We estimate that the number of independent resolution elements in the final image – measured as the half-maximum area of the two-photon point spread function divided by the area imaged – to be ~3200.